Drug Permeability: From the Blood–Brain Barrier to the Peripheral Nerve Barriers. Issue 4 (9th February 2023) - Sun, Yifei; Zabihi, Mahmood; Li, Qi; Li, Xiaosi; Kim, Brandon J.; Ubogu, Eroboghene E.; Raja, Srinivasa N.; Wesselmann, Ursula; Zhao, Chao
Abstract: Drug delivery into the peripheral nerves and nerve roots has important implications for effective local anesthesia and treatment of peripheral neuropathies and chronic neuropathic pain. Similar to drugs that need to cross the blood–brain barrier (BBB) and blood–spinal cord barrier to gain access to the central nervous system (CNS), drugs must cross the peripheral nerve barriers (PNBs), formed by the perineurium and blood–nerve barrier to modulate peripheral axons. Despite significant progress made to develop effective strategies to enhance BBB permeability in therapeutic drug design, efforts to enhance drug permeability and retention in peripheral nerves and nerve roots are relatively understudied. Guided by knowledge describing structural, molecular, and functional similarities between restrictive neural barriers in the CNS and peripheral nervous system, it is hypothesized that certain CNS drug delivery strategies are adaptable for peripheral nerve drug delivery. Here, the molecular, structural, and functional similarities and differences between the BBB and PNB are described, existing CNS and peripheral nerve drug delivery strategies are summarized and compared, and the potential application of selected CNS delivery strategies to improve efficacious drug entry for peripheral nerve disorders is discussed. Abstract : The molecular, structural, and functional similarities and differences between the blood–brain barrier and peripheral nerve barrier are described, existing central nervous system (CNS) and peripheral nerve drug delivery strategies are summarized and compared, and the potential application of selected CNS delivery strategies to improve efficacious drug entry for peripheral nerve disorders is discussed.